2018
DOI: 10.1161/atvbaha.117.310222
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Function in Cardiovascular Disease and Diabetes Mellitus

Abstract: e10C ardiovascular disease (CVD) is the most common cause of death worldwide.1 Major CVD risk factors are hypertension, smoking, physical inactivity, abnormal glucose levels/diabetes mellitus, and dyslipidemia. Among these, dyslipidemia characterized by a low level of HDL-C (high-density lipoprotein cholesterol) is strongly and inversely correlated with CVD risk, 2-4 and low HDL-C levels is part of the atherogenic dyslipidemia complex associated with diabetes mellitus.5 These observations triggered intense int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 92 publications
(111 reference statements)
0
33
0
Order By: Relevance
“…However, recent evidence has shown that a low HDL concentration is associated with an increased cardiovascular risk, but that a high HDL concentration does not have a protective effect and could even be dangerous, as has been shown in the general population and in individuals with T1DM [106,116,117]. These unexpected results may be explained by the existence of different HDL subspecies with different functions [118]. Thus, it may be beneficial to directly measure HDL function, such as its role in promoting reverse cholesterol transport (the net movement of cholesterol from peripheral tissues to the liver to be excreted through the bile) [118].…”
Section: Changes In Lipid Metabolism At the Origin Of Atherosclerosismentioning
confidence: 94%
See 3 more Smart Citations
“…However, recent evidence has shown that a low HDL concentration is associated with an increased cardiovascular risk, but that a high HDL concentration does not have a protective effect and could even be dangerous, as has been shown in the general population and in individuals with T1DM [106,116,117]. These unexpected results may be explained by the existence of different HDL subspecies with different functions [118]. Thus, it may be beneficial to directly measure HDL function, such as its role in promoting reverse cholesterol transport (the net movement of cholesterol from peripheral tissues to the liver to be excreted through the bile) [118].…”
Section: Changes In Lipid Metabolism At the Origin Of Atherosclerosismentioning
confidence: 94%
“…These unexpected results may be explained by the existence of different HDL subspecies with different functions [118]. Thus, it may be beneficial to directly measure HDL function, such as its role in promoting reverse cholesterol transport (the net movement of cholesterol from peripheral tissues to the liver to be excreted through the bile) [118]. For example, when the macrophages present in artery walls accumulate excess cholesterol, the ATP-binding cassette transporters A1 and G1 are induced and this results in the efflux of cholesterol from the macrophages to the HDL [118].…”
Section: Changes In Lipid Metabolism At the Origin Of Atherosclerosismentioning
confidence: 98%
See 2 more Smart Citations
“…High-density lipoprotein (HDL) is generally considered to be anti-atherogenic and is known to prevent endothelial dysfunction [51]. Free SDMA has been reported to cause the transformation of physiological HDL to an abnormal atherogenic HDL, which reduces endothelial NO availability by enhancing endothelial superoxide production via activation of the toll-like receptor-2 (TLR-2) [52].…”
Section: Arg Dimethylation and Growth And Inflammatory Factorsmentioning
confidence: 99%